2017
DOI: 10.1371/journal.pone.0176466
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in COL1A1 and COL1A2 and dental aberrations in children and adolescents with osteogenesis imperfecta – A retrospective cohort study

Abstract: Osteogenesis imperfecta (OI) is a heterogeneous group of disorders of connective tissue, caused mainly by mutations in the collagen I genes (COL1A1 and COL1A2). Dentinogenesis imperfecta (DGI) and other dental aberrations are common features of OI. We investigated the association between collagen I mutations and DGI, taurodontism, and retention of permanent second molars in a retrospective cohort of 152 unrelated children and adolescents with OI. The clinical examination included radiographic evaluations. Teet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 42 publications
8
85
1
1
Order By: Relevance
“…Craniofacial and dentoalveolar abnormalities are present in mild, moderate, and severe types of OI. Cephalometric studies have revealed that dentoalveolar structures and the condylar processes are often vertically underdeveloped in OI types III and IV . Clinically, the hypoplastic maxilla and reduced vertical and transverse dimensions result in a malocclusion, such as bilateral open bite or cross bite, and counterclockwise (overclosing) rotation of the mandible .…”
Section: Introductionmentioning
confidence: 99%
“…Craniofacial and dentoalveolar abnormalities are present in mild, moderate, and severe types of OI. Cephalometric studies have revealed that dentoalveolar structures and the condylar processes are often vertically underdeveloped in OI types III and IV . Clinically, the hypoplastic maxilla and reduced vertical and transverse dimensions result in a malocclusion, such as bilateral open bite or cross bite, and counterclockwise (overclosing) rotation of the mandible .…”
Section: Introductionmentioning
confidence: 99%
“…A study by Lagana et al [21] reported an impaction prevalence of 3.9% in a group of 4706 aged 8−12-years. Retention of permanent second molars is a frequent finding in OI [5, 6, 22], but was not found in any individuals in this cohort. Pulpal obliteration occurred in 100% of the children in the present study.…”
Section: Discussionmentioning
confidence: 74%
“…Clinically, the following signs were evaluated: retained teeth (failure of eruption), malocclusion, and DGI indicators – pathologic discoloration, attrition, and fractures. Radiographically, these signs were evaluated: number of tooth germs, extended pulp chambers (taurodontism), and DGI indicators – bulbous crowns with cervical constriction, pulpal obliteration, and short roots [5]. Individuals with suspected OI were referred to the national OI multidisciplinary pediatric team at Astrid Lindgren Children’s Hospital for further examination and diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A frequent dental abnormality in OI is dentinogenesis imperfecta, which is caused by dysplastic dentin and can lead to dental discoloration, tooth fracture, and attrition . Genotype–phenotype correlation studies show that the large majority of patients with OI types III and IV caused by qualitative mutations have dentinogenesis imperfecta, whereas only a small minority of individuals with COL1A1 haploinsufficiency mutations have dentinogenesis imperfecta that is visible on clinical inspection . Beyond dentinogenesis imperfecta, tooth agenesis is a common finding in OI .…”
Section: Other Disease Manifestationsmentioning
confidence: 99%